FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KOMPLIKASI PERSALINAN PERVAGINAM DI RSUD DR. PIRNGADI MEDAN TAHUN 2014 - gravika dian; Sri Rahayu Sanusi; Yusniwarti Yusad (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
ABSTRACT Maternal Mortality Rate (MMR) is a basic indicator of obstetric care or health of the woman at the age of produktif, more than 90% of maternal deaths due to complications that often occur at or around birth. Birth Complications is a deviation from the normal state, which directly cause morbidity and maternal mortality, because of the direct effect of the birth. This study aims to determine the factors that influence the occurrence of complications of labor with risk factor approach in the General Hospital. Pirngadi Medan in 2014. This research is a descriptive analytic case control design, namely selecting case and control respondents respondents uncomplicated birth. The number of respondents in 576 birth by taking samples in random and analyzed with the test statististik Odds Ratio (OR) and chi-square test. The results showed that there was correlation between age ( ρ =0,001, OR=5,875, parity (ρ =0,048, OR=2,214), pregnancy history ( ρ =0,028, OR=2,435) and disease history ( ρ =0,001, OR=8,000) with birth complications, whereas education and antenatal care no relationship. Suggested to health care workers in hospitals to improve counseling and provide information to pregnant women about the condition in women with complications of childbirth and improve services so that hospital is always ready to serve the referral of patients with complications of birth.